Calculating Variations in Biological Effectiveness for a 62 MeV Proton Beam - Carante, Mario Pietro; Ballarini, Francesca (Frontiers in Oncology, 2016)
A biophysical model of radiation-induced cell death and chromosome aberrations (called BIANCA, BIophysical ANalysis of Cell death and chromosome Aberrations) was further developed and applied to therapeutic protons. The model assumes a pivotal role of DNA cluster damage, which can lead to clonogenic cell death following three main steps: i) a DNA “Cluster Lesion” (CL) produces two independent chromosome fragments; ii) fragment mis-rejoining within a threshold distance d gives rise to chromosome aberrations; iii) certain aberration types (dicentrics, rings and large deletions) lead to clonogenic inactivation. The yield of CLs and the probability, f, that a chromosome fragment remains un-rejoined even if other fragment(s) are present within d, were adjustable parameters. The model, implemented as a MC code providing simulated dose-responses directly comparable with experimental data, was applied to pristine and modulated Bragg peaks of the proton beam used to treat eye melanoma at INFN-LNS in Catania, Italy. Experimental survival curves for AG01522 cells exposed to the Catania beam were reproduced, supporting the model assumptions. Furthermore, cell death and chromosome aberrations at different depths along a SOBP (Spread-Out Bragg Peak) dose profile were predicted. Both endpoints showed an increase along the plateau, and high levels of damage were found also beyond the distal dose fall-off, due to low-energy protons. Cell death and chromosome aberrations were also predicted for V79 cells, in the same irradiation scenario as that used for AG01522 cells. In line with other studies, this work indicated that assuming a constant RBE along a proton SOBP may be sub-optimal. Furthermore, it provided qualitative and quantitative evaluations of the dependence of the beam effectiveness on the considered endpoint and dose. More generally, this work represents an example of therapeutic beam characterization avoiding the use of experimental RBE values, which can be source of uncertainties.